[Miklós Németh 5]
picnic & procession in May, soldieers drilling, flame-thrower, transceiver, pontoon-bridge, scout-girls, tents, performances, competitions, cups, Uránia filmtheater, old peasent with pipe, speech&many people, celebration, performances, musicians,